Angiolymphoid hyperplasia with eosinophilia. - Garofalo, L. (European Journal of Pediatric Dermatology, 2016)
Angiolymphoid hyperplasia with eosinophilia is a benign proliferation of vessels associated with a lymphocytic infiltrate and eosinophils (2). It affects young adults more often females. We do not know the cause but it is believed a reactive process in response to various stimuli in predisposed subjects. The most frequently affected site are the head and neck, mainly the periauricular region. The clinical course is variable sometimes with spontaneous regression in months or after a much longer period. The best treatment is surgical excision when possible, but is susceptible to various treatments such as laser, methotrexate (1), topical or intralesional immunosuppressants. Angiolymphoid hyperplasia with eosinophilia should be differentiated from Kimura’s disease in which the lesions are deeper, are associated with lymphadenopathy and frequently peripheral eosinophilia, and lack epithelioid endothelial cells.